A neural network combined with sliding mode controller for the two-wheel self-balancing robot - Duc-Minh Nguyen; Van-Tiem Nguyen; Trong-Thang Nguyen (IAES International Journal of Artificial Intelligence (IJ-AI), 2021)
This article presents the sliding control method combined with the selfadjusting neural network to compensate for noise to improve the control system's quality for the two-wheel self-balancing robot. Firstly, the dynamic equations of the two-wheel self-balancing robot built by Euler–Lagrange is the basis for offering control laws with a neural network of noise compensation. After disturbance-compensating, the sliding mode controller is applied to control quickly the two-wheel self-balancing robot reached the desired position. The stability of the proposed system is proved based on the Lyapunov theory. Finally, the simulation results will confirm the effectiveness and correctness of the control method suggested by the authors.